TESTOSTERONE TO ESTRADIOL (T/E2 ) RATIO, AS A LABORATORY PREDICTOR IN INFERTILE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Polycystic ovary syndrome is a common endocrine disease in women, characterized by heterogeneous presentation of hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. This study was carried out to assess plasma levels of testosterone, estradiol calcium and cholesterol levels among females with polycystic ovarian syndrome (PCOs).Forty females aged 18-35 years diagnosed by ultrasonography and Anti-Müllerian hormone  (AMH) test in Alsir Abu-Hassancenter for fertility in Khartoum State, and forty apparently healthy individuals as control group participated in this study.Plasma testosterone and estradiol measured by using ELISA, cholesterol measured by BS-380 chemistry analyzer, and calcium by colorimetric method. Results were analyzed using statistical package for social science (SPSS), computer programmed version 21.   The study showed that, the mean plasma levels of testosterone and T/E2 ratio were significantly increased in PCOs female patients. For testosterone (1.4±1.1 versus 0.87±0.65ng/ml, p-Value =0.011). For T/E2 ratio (0.019±0.015 versus 0.01±0.008 ng/pg,p-Value =0.022). Also the finding of this study showed insignificant difference in estradiol levels between PCOs compared with control group. (Mean±SD: 86±39versus 101±38.6 pg/ml) respectively with P. Value 0.086. The mean  plasma levels of cholesterol was significantly increased in PCOs female patients. (Mean±SD: 207.6±33.4 versus112±33.4  mmoL /L) respectively with P.vale 0.000. The  mean  level  of plasma  calcium  was  significantly  decreased  (p.value  0.000). It  is  concluded  that:  the plasma  levels  of testosterone, T/E2 ratio and cholesterol are higher in PCOs female patients, while calcium level decreased.